Tri Kaya Parisudha as a Remedies to the Agency Problem - I Gusti Ayu Ngurah Pradnyadevi Utami; Zahroh Naimah; Anak Agung Dwi Widyani (Jurnal Ilmiah Akuntansi, 2023)
This conceptual paper proposes a novel approach to mitigate agency problems by incorporating the principles of Tri Kaya Parisudha from Balinese Hinduism. Tri Kaya Parisudha underscores the purification of thought (manacika parisudha), speech (wacika parisudha), and action (kayika parisudha). The paper explores relevant verses that can be applied to alleviate agency problems in the context of corporate governance. The application of Tri Kaya Parisudha values is expected to foster self-discipline, enhance ethical behavior, and cultivate a harmonious and ethical corporate environment. By aligning actions, speech, and thoughts with these higher principles, individuals are anticipated to reduce potential agency problems and contribute to the promotion of integrity in decision-making processes. Notably, to the best of the author's knowledge, there is a dearth of published literature addressing the reduction of agency problems through the lens of Tri Kaya Parisudha. This paper seeks to fill this gap by offering a unique perspective on the integration of religious values for improved corporate governance.